2006
DOI: 10.1038/oby.2006.147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise on Hepatic Gene Expression in an Obese Mouse Model Using cDNA Microarrays

Abstract: To understand the molecular mechanisms involved in the effect of exercise training, we examined hepatic transcriptional profiles using cDNA microarrays in exercise-trained and untrained mice with diet-induced obesity. C57BL/6J male mice (n ϭ 10/group) were fed with a normal diet, high-fat diet (HFD), or HFD with exercise training for 12 weeks. The expression level of ϳ10,000 transcripts in liver tissues from each group was assessed using cDNA microarray analysis. Exercise training improved lipid profiles and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…Forced exercise can define work but is associated with less volume and may be more stressful. Nonetheless, both paradigms improve insulin sensitivity, reduce hepatic fat, and alter liver gene expression (6,912). Our group has also shown that acute exercise increases plasma glucagon (20,23).…”
Section: Discussionmentioning
confidence: 99%
“…Forced exercise can define work but is associated with less volume and may be more stressful. Nonetheless, both paradigms improve insulin sensitivity, reduce hepatic fat, and alter liver gene expression (6,912). Our group has also shown that acute exercise increases plasma glucagon (20,23).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, physical activity, which reduces intra-abdominal adiposity effectively, increases the expression of LPIN1. 30 In conclusion, our study demonstrated a significant association between rs10495584 and systolic blood pressure in men. Although this SNP is in high LD with rs11524, in which the major allele forms an exonic splicing silencer sequence, it remains to be established how these two SNPs affect blood pressure by alternative splicing.…”
Section: Discussionmentioning
confidence: 85%
“…Compared with the numerous reports on the transcriptional regulation of genes in the working muscle, remarkably little data on exercise-induced gene expression in the liver are available. Some studies have investigated the effects of long-term exercise training on hepatic expression of metabolic enzymes in obese or diabetic rodents [21][22][23]. The expression of genes involved in the regulation of glucose and fatty acid metabolism was also found to be regulated by one single bout of exercise.…”
Section: Introductionmentioning
confidence: 99%